Investigation of the Bearing Capacity and Collapsibility of Gypseous Soil Using Geotextile Reinforcement - Qasim Al-Obaidi; Makki Mohsen; Ayad Asker (Engineering and Technology Journal, 2022)
This study aims to increase the bearing capacity of the soil by using geosynthetics in a single, double, or triple distribution pattern. The gypseous soil samples were brought from a site near Sawa Lake in Al-Muthanna Governorate with a gypsum content of about (37%), the Soil-Model apparatus of dimensions (60 × 60 × 50) cm with the proposed square footing of dimensions (10 × 10) cm are used in the experimental program of this study. To achieve this goal, a series of (48) different model tests were used on gypseous soil subjected to vertical stress in both dry and wet (saturation) conditions. Depending on the results of load-settlement curves relationships, the ultimate bearing capacity of dry and wet gypseous soil models was determined using the Two Tangent Intersection technique. The results also showed that the number of geotextile layers and the relative density of the gypseous soil samples significantly impact the improvement of the bearing capacity of gypseous soil models. Furthermore, the results showed that the improvement ratio in bearing capacity (BCR%) for gypseous soil models tested after being reinforced with geotextile layer for dry and wet (saturation)  at relative density (RD) of 30% and  60%  in single, double and triple distribution pattern. The percentage of the improvement in the wet case was higher than in the dry case. It was 143 % in the wet case when using triple-layer geotextile at different depths of reinforcement, while it was 96 % in the dry case.